Fraud Triangle Perspective: Detecting Financial Statement Fraud Using the Beneish M-Score Model in Property and Real Estate Companies Listed on the Indonesia Stock Exchange - Erlina W Djatnicka; Jamian Purba; Dian Sulistyorini Wulandari (East Asian Journal of Multidisciplinary Research, 2023)
This study aims to determine the effect of Financial Stability, Financial Targets, and External Pressure on Financial Statement Fraud in Property and Real Estate companies listed on the Indonesia Stock Exchange (BEI) in 2015–2017. The research method used in this study is quantitative. The data used is secondary data in the form of financial statements and annual reports. The sampling technique in this study was the purposive sampling method, where the sample selection was based on certain criteria. The samples used in this study amounted to 30 property and Real Estate companies listed on the Indonesia Stock Exchange in 2015–2017. The analysis technique in this study uses logistic regression analysis. The results of the analysis show that financial stability has a positive effect on fraudulent financial statements, financial targets have a positive effect on fraudulent financial statements, and external pressure has no positive effect on fraudulent financial statements.